Information security of intellectual transport systems - Лахно, Валерій Анатолійович (Ukrainian Information Security Research Journal, 2015)
This paper contains research results aimed at further de-velopment of models for information and communication environment, intellectual transport systems threat detec-tion and information security improvement in the emerg-ing unified information-communication environment, implementation of new and upgrading existing information systems in transport and increase the number of destabilizing effects on the availability, confidentiality and integrity of information. The analysis of traditional meth-ods of solving this task is conducted. The construction method of linear on parameters regressive mechanism of inference is offered for a consulting model with fuzzy data’s. Offered diagnostic model and the algorithm provides more precise determining of parameters of infor-mation security, which will result in increasing of level of protection of intellectual transport systems.